2023
DOI: 10.6004/jnccn.2022.7071
|View full text |Cite
|
Sign up to set email alerts
|

Prevalent Pseudoprogression and Pseudoresidue in Patients With Rectal Cancer Treated With Neoadjuvant Immune Checkpoint Inhibitors

Abstract: Background: Immune checkpoint inhibitor (ICI) treatment in patients with microsatellite instability-high/mismatch repair deficient (MSI-H/dMMR) tumors holds promise in reshaping organ preservation in rectal cancer. However, the benefits are accompanied by distinctive patterns of response, introducing a dilemma in the response evaluation for clinical decision-making. Patients and Methods: Patients with locally advanced rectal cancer with MSI-H/dMMR tumors receiving neoadjuvant ICI (nICI) treatment (n=13) and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Beyond superficial biopsies, TRUS-TCB provides comprehensive whole-layer pathological insights. Combined with superficial biopsies, TRUS-TCB aids clinicians in “watch-and-wait” determinations for suspicious post-immunotherapy lesions, contributing to sphincter preservation 28 . A trial participant in our study receiving immunotherapy echoed previous findings—TRUS-TCB predicted pCR accurately, while MRI indicated residue.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond superficial biopsies, TRUS-TCB provides comprehensive whole-layer pathological insights. Combined with superficial biopsies, TRUS-TCB aids clinicians in “watch-and-wait” determinations for suspicious post-immunotherapy lesions, contributing to sphincter preservation 28 . A trial participant in our study receiving immunotherapy echoed previous findings—TRUS-TCB predicted pCR accurately, while MRI indicated residue.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it should be noted that preoperative imaging examinations may not accurately assess tumor volume in patients receiving ICIs due to potential signs of tumor pseudoprogression resulting from immune activation. Combining circulating tumor DNA and blood-based tumor markers is an alternative approach to re ect the true response to ICIs treatment (35). On the other hand, the watch-and-wait (WW) strategy under close surveillance is considered an alternative for patients achieving cCR.…”
Section: Discussionmentioning
confidence: 99%
“…Xie et al . 78 revealed that pseudoprogression and pseudoresidue were present in three CRC patients (23.1%) and 10 CRC patients (76.9%), respectively.…”
Section: Clinical Advances In Neoadjuvant Immunotherapy In Gastrointe...mentioning
confidence: 99%